DETERMINANTS OF EARNINGS PERSISTENCE WITH CAPITAL STRUCTURE AS INTERVENING VARIABLE OF MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE PERIOD 2015 - 2019 - Elsa Lasrya; Teddy Chandra; Harry Patuan Panjaitan (Journal of Applied Business and Technology, 2021)
The purpose of this study was to determine the effect of cash flow volatility, sales volatility, operating cycle, and firm size on the capital structure and earnings persistence of manufacturing companies in Indonesia. Based on the purposive sampling method, the samples obtained were 138 companies. The data collection technique in this research is literature study. The data analysis method used is multiple regression. The results showed that partially, the variables of cash flow volatility, sales volatility and firm size had a positive and insignificant effect on capital structure, the operating cycle had a negative and insignificant effect on capital structure. While the variables of cash flow volatility, sales volatility, operating cycle, firm size, capital structure have a negative and insignificant to earnings persistence of manufacturing companies on the Indonesia Stock Exchange.